Okul Psikolojik Danışman Adaylarının Genel Öz- Yeterlik ve Özel Eğitimde Rehberlik ve Psikolojik Danışmanlığa İlişkin Öz-Yeterlik İnançları Arasındaki İlişkinin İncelenmesi - Yılmaz Bingöl, Tuğba (OPUS, 2018)
Bu araştırmada okul psikolojik danışman adaylarının genel öz-yeterlik ve özel eğitime dair öz-yeterlikleri arasındaki ilişki incelenmiş ve özel eğitime dair öz-yeterlik algılarının demografik değişkenlere göre farklılaşıp farklılaşmadığı araştırılmıştır. Araştırma 284 üniversite öğrencisiyle (220 kız, 64 erkek) yürütülmüştür. Araştırma, genel tarama yöntemine göre yürütülmüştür. Verilerin toplanması için araştırmacı tarafından hazırlanan Kişisel Bilgi Formu, Aypay (2010)tarafından geliştirilen Genel Öz-yeterlik Ölçeği (GÖY) ve Yüksel (2010) tarafından uyarlanan Rehber Öğretmenlerin Özel Eğitime İlişkin Öz-yeterlik Ölçeği (RÖÖEÖY) kullanılmıştır. Araştırma sonuçlarına göre katılımcıların genel öz-yeterllik ölçeğinden aldıkları ortalama puan 31,37 (Ss=4.67), özel eğitime ilişkin öz-yeterlik ölçeğinden aldıkları puan ortalaması ise 115,94’dür (Ss=31.29). Ayrıca okul psikolojik danışman adaylarının özel eğitime dair öz-yeterlik inançları, yaş [F(4-279) =7,75, p< .05] ve sınıf [F(2-281)=39,065, p< .05] değişkenlerine göre farklılık göstermektedir. Cinsiyete göre ise anlamlı bir farklılık çıkmamıştır (t= ,126, p> .05). Katılımcıların genel öz-yeterlik inançları ve özel eğitime dair öz-yeterlik inançları arasında, istatistiksel olarak anlamlı bir ilişki olmadığı görülmüştür (p>.05).

In this research, the relationship between general self-efficacy of school psychological counselor candidates and self-efficacy beliefs of that regarding special education was investigated. Also, it has been examined whether the school psychological counselor candidates' self-efficacy beliefs regarding special education differ according to the demographic variables or not. The research was conducted based on the general screening method with 284 university students (220 female, 64 male) studying. In the data collection process personal information form prepared by the researcher, General Self-efficacy Scale (GSE) developed by Aypay (2010) and School Counselors’ Self-Efficacy Scale regarding Special Education (SCSSSE) adapted by Yüksel (2010) were used. According to the results of the research, the average score of the participants on the general self-efficacy scale was 31.37 (Sd= 4.67) and the average score on the self-efficacy scale on the special education was 115.94 (Sd = 31.29). Results indicated that the self-efficacy beliefs of school psychological counselor candidates regarding special education varied according to age [F(4-279) =7,75, p< .05] and class [F(2-281)=39,065, p< .05] variables. According to sex, there was no significant difference (t =, 126, p> .05). There was no statistically significant relationship was found between participants' general self-efficacy beliefs and self-efficacy beliefs regarding special education (p>.05).
Investigation of The Relationship Between General Self-Efficacy of School Psychological Counselor Candidates and Self-Efficacy Beliefs of That Regarding Special Education
Keywords: Öz-Yeterlik; Özel Eğitim Öz-Yeterliği; Okul Psikolojik Danışmanı; Self-Efficacy; Self-Efficacy of Regarding Special Education; School Psychological Counselor